Văn học Việt Nam thế kỷ XX - Nguyễn, Cừ (Văn học, 2010)
Giới thiệu các tác phẩm thơ của nhiều tác giả: Nguyễn Thị Thiếu Anh, Hoàng Hương Bình, Nguyễn Bính, Thái Can, Nguyễn Đức Cảnh, Văn Cao, Huy Cận...